Dermatofibrosarcoma in glabella: An uncommon location - Carlos Eduardo Baldini; Mario Augusto Ferrari de Castro; Rogério Aparecido Dedivitis (Revista Brasileira de Cirurgia Plástica, 2023)
Dermatofibrosarcoma is a rare cancer with a slow growth pattern and aggressive tissue invasion. The treatment for this condition involves surgical intervention to achieve clear margins. In this particular case, we have a 60-year-old man who had a mass in the glabella area that was excised twice under local anesthesia at a different facility. The results of both biopsies indicated dermatofibroma. However, the patient experienced a new recurrence, and during the immunohistochemistry analysis of the initial excision, it was revealed to be dermatofibrosarcoma. As a result, a broad excision was performed until negative margins were obtained based on frozen sections. Additionally, a frontal flap was employed to reconstruct the surgical defect. The outcome of the treatment was deemed successful, without complications.